Digital Wallets and Student Finances: Analyzing Behavioral Shifts in the Era of Cashless Payments - Ahmad Hafidh Saiful Fikri, Aula; Sholeh, Maimun; Susilowati, Nenden; Roestam Afandi, Muhammad; Febrianto, Indra (Yayasan Sinergi Kawula Muda, 2025)
The development of financial technology (fintech) has brought significant changes to people's transaction patterns, particularly among university students, with the increasing use of digital wallets. This phenomenon is influenced by various factors, including digital literacy, financial attitude, herd behavior, and these factors impact on financial well-being. Therefore, this study aims to construct a structural model of digital wallet usage and how it impacts the financial well-being of students. This research uses a quantitative approach with the Structural Equation Modeling-Partial Least Squares (SEM-PLS) method to examine the relationships between variables. Data was collected through the distribution of questionnaires to students who actively use digital wallets. The results show that digital literacy has the largest total effect on financial well-being through two pathways: a direct influence and an indirect influence through the use of digital wallets. The total effect of digital literacy is high, making it the dominant predictor in the model. The research results show an R² value for the digital wallet usage variable of 0.508, which falls into the moderate category, while for the financial well-being variable it is 0.723, which falls into the high category. Digital literacy (LD) has established itself as the most fundamental determinant in the digital financial ecosystem. It serves not only as the primary driver of digital wallet (PDD) adoption by enhancing perceived usefulness and ease of use, consistent with the extended technology acceptance model, but also contributes directly and significantly to improving financial well-being (FWB) by facilitating access to financial information and products, aligning with the digital divide theory.